Ultraviolet-proof display screen protective film
By using modified nano zinc oxide, modified nano titanium dioxide and modified melanin powder in the display protective film, the problem of insufficient UV and blue light protection performance in the prior art is solved, and a more stable barrier effect and higher hardness and weather resistance are achieved.
Patent Information
- Application Number
- CN202411927065.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing display protective film has insufficient performance in terms of UV protection and blue light protection, and the commonly used organic UV absorbers are unstable during use, easy to precipitate or precipitate, affecting the light transmittance and clarity.
Using a composite film including a polyurethane layer and a modified polyurethane acrylate layer, the modified nano zinc oxide and modified nanotitanium dioxide are used as the ultraviolet absorber in the modified polyurethane acrylate layer, and the modified melanin powder is added to the composite adhesive layer to improve the UV and blue light resistance.
It achieves a more stable ultraviolet and blue light barrier effect, improves the hardness and weather resistance of the protective film, and avoids the instability of organic ultraviolet absorbers.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective films, and in particular relates to an ultraviolet-proof display screen protective film. Background Art
[0002] With the rapid development of electronic technology, electronic products such as mobile phones, computers, and televisions have become almost necessities for people. People need to spend a lot of time facing these electronic products every day. However, the light emitted by the display screens of these electronic products contains ultraviolet rays and blue light that are very harmful to the human body.
[0003] Ultraviolet rays are electromagnetic waves with a wavelength of 100-400nm. They cannot cause vision problems, but they are a type of harmful light. Ultraviolet rays are very harmful to human eyes. According to surveys, the effects of ultraviolet rays on people are lifelong. Long-term exposure to harmful ultraviolet radiation can induce eye diseases such as cataracts and macular degeneration. These eye diseases are one of the main causes of blindness after the age of 60. In addition, ultraviolet rays also have an impact on the central nervous system. When ultraviolet rays act on the central nervous system, headaches, dizziness, and fever may occur.
[0004] Blue light refers to high-energy light with a wavelength of 400-500nm, which can penetrate the lens to reach the retina, causing the retinal pigment epithelial cells to die, resulting in a lack of nutrients for the photosensitive cells, thus causing irreversible vision damage. Blue light has a high probability of scattering when encountering tiny particles in the air, which can easily produce glare. In addition, blue light can stimulate the brain, inhibit the secretion of melatonin and increase the production of adrenal cortex hormones, thereby disrupting the balance of hormone secretion and directly affecting sleep quality.
[0005] Generally, in order to make the protective film have the effect of ultraviolet absorption, ultraviolet absorbers are added to the formula. The added ultraviolet absorbers are usually high molecular organic substances, which are prone to mismatch with the formula system and easy to precipitate or settle during use, reducing the light transmittance and clarity of the protective film. Moreover, a large amount needs to be added to achieve the effect, which will reduce the physical properties of the protective film to a certain extent, and the weather resistance is not strong. It is easy to precipitate small molecules after long-term use. Therefore, inventing a display screen protective film with anti-ultraviolet and anti-blue light properties is of great significance to protecting human health. Summary of the invention
[0006] The object of the present invention is to provide an ultraviolet resistant display screen protective film to solve the above problem.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A UV-proof display screen protective film, which is a composite film composed of a polyurethane layer and a modified polyurethane acrylate layer, wherein the polyurethane layer and the modified polyurethane acrylate layer are composited with a composite adhesive layer; the modified polyurethane acrylate layer comprises modified nano zinc oxide and modified nano titanium dioxide; and the composite adhesive layer is an adhesive coating comprising modified melanin powder and PVB adhesive.
[0009] Furthermore, the polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 1-3 parts of modified sepiolite powder, 2 parts of coupling agent, 1 part of dispersant, and 3 parts of lubricant.
[0010] Furthermore, the modified sepiolite powder is prepared by the following steps:
[0011] The sepiolite is calcined at 500-600°C for 1 hour, and after cooling, it is crushed in a ball mill and sieved to obtain nano-grade sepiolite powder; the sepiolite powder is added to a mixed solution of pentanediol and ethyl acetate with a mass concentration of 15%, stirred and mixed to uniformly disperse to obtain a dispersion; then hydrochloric acid accounting for 1-2% of the mass of the dispersion is added to the dispersion, ultrasonically treated for 5-10 minutes, filtered, washed with deionized water, and dried to obtain modified sepiolite powder.
[0012] Furthermore, the mass ratio of pentanediol to ethyl acetate in the mixed solution of pentanediol and ethyl acetate is 3:1.
[0013] Modified sepiolite powder can improve the mechanical stability and chemical stability of the polyurethane layer, which is beneficial to improving the hardness of the protective film.
[0014] Further, the coupling agent is one of SG-Al821, DL-411 and DL-411AF;
[0015] The dispersant is ethylene-vinyl acetate copolymer;
[0016] The lubricant is stearic acid.
[0017] Furthermore, the modified polyurethane acrylate layer comprises modified polyurethane acrylate containing modified nano zinc oxide and modified nano titanium dioxide, and the preparation steps of the modified polyurethane acrylate are:
[0018] Add 0.5-1 parts of nano zinc oxide and 0.5-1 parts of nano titanium dioxide by weight to 1-2 parts of methyl methacrylate, 1-2 parts of n-butyl acrylate and 0.1-0.2 parts of n-octadecyl acrylate, and stir for 2-3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide; heat the solution to 70-80°C, add 0.05 parts of potassium persulfate and 5 parts of polyurethane acrylate, and react for 3-5 hours; then heat the solution to 90-100°C and react for 1-2 hours to obtain modified polyurethane acrylate.
[0019] Furthermore, the size of the nano zinc oxide is 60-80nm, and the size of the nano titanium dioxide is 60-80nm.
[0020] Nano-level zinc oxide and titanium dioxide both have the ability to absorb ultraviolet rays. After being modified and grafted onto polyurethane acrylate, polyurethane acrylate can acquire the property of absorbing ultraviolet light. Since nano zinc oxide and nano titanium dioxide also have good visible light transmittance, the optical properties of the protective film will not be negatively affected. In addition, as metal oxides, zinc oxide and titanium dioxide can bring significant improvements in physical properties compared to organic substances, especially in improving the hardness and wear resistance of the coating.
[0021] Furthermore, the polyurethane acrylate has a functionality of 6-9.
[0022] When the functionality of polyurethane acrylate is low, its cross-linking density is low, which helps to reduce shrinkage during the curing process, thereby enhancing the adhesion between the protective film and the substrate; however, this low functionality will also lead to a decrease in its physical properties; on the contrary, if the functionality of polyurethane acrylate is high, its cross-linking density will increase, thereby improving the physical properties; but at the same time, the curing shrinkage rate will also increase accordingly, which may cause the protective film to have a large warping, and in severe cases even affect the normal use of the protective film; therefore, in the present invention, we select polyurethane acrylate with a functionality of 6-9.
[0023] Furthermore, the composite adhesive layer comprises the following raw materials in parts by weight:
[0024] 15 parts of PVB adhesive, 20 parts of ethyl acetate, 3-5 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid.
[0025] Furthermore, the modified melanin powder is prepared by the following steps:
[0026] (1) 8-10 parts of melanin powder are uniformly dispersed in 80 parts of dimethyl sulfoxide by weight, 1-3 parts of sodium citrate are added, and the mixture is stirred and reacted at 120-130° C. for 30-60 minutes; 30-40 parts of n-butanol and 1-2 parts of dodecyl bromide are added, and the mixture is stirred and reacted at 100° C. for 30-60 minutes; 10-20 parts of polydimethylsiloxane and 1-3 parts of disodium ethylenediaminetetraacetate are added, and the mixture is stirred and reacted at 120° C. for 30-60 minutes; after the reaction is completed, the mixture is filtered, washed, and dried to obtain a primary product;
[0027] (2) adding 1-3 parts of the initial product to 8-10 parts of dimethylformamide, and then adding 1-2 parts of maleic anhydride, 1-3 parts of fumaric acid and 0.3 parts of citric acid, stirring and reacting at 60-70° C. for 20-30 minutes; after the reaction is completed, filtering, washing and drying to obtain modified melanin powder.
[0028] Melanin powder has the effect of absorbing blue light. Modifying the melanin powder can improve its dispersibility, thereby enhancing its ability to absorb blue light.
[0029] Beneficial effects of the present invention:
[0030] (1) The present invention grafts nano zinc oxide and nano titanium dioxide onto polyurethane acrylate after modification as ultraviolet absorbers to replace the commonly used organic ultraviolet absorbers. Compared with organic ultraviolet absorbers, nano zinc oxide and nano titanium dioxide are more stable in weather resistance and do not need to worry about small molecule absorption as the use time increases, or failure due to temperature changes. In addition, the modified nano zinc oxide and nano titanium dioxide have good compatibility with polyurethane acrylate and will not agglomerate, so they can better protect against ultraviolet rays. On the other hand, as metal oxides, zinc oxide and titanium dioxide can bring significant improvements in physical properties, especially in improving the hardness and wear resistance of the coating, compared with organic substances.
[0031] (2) The present invention can improve the mechanical stability and chemical stability of the polyurethane layer by adding modified sepiolite powder to the polyurethane layer, which is beneficial to improving the hardness of the protective film; the present invention adds modified melanin powder to the composite adhesive. The melanin powder has a blue light absorption effect. Modification of the melanin powder can improve its dispersibility, thereby enhancing its blue light absorption effect, and further endowing the protective film with a good anti-blue light effect. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] The present embodiment provides an anti-ultraviolet display screen protective film, which is a composite film composed of a polyurethane layer and a modified polyurethane acrylate layer, wherein the polyurethane layer and the modified polyurethane acrylate layer are composited with a composite adhesive layer; the modified polyurethane acrylate layer includes modified nano zinc oxide and modified nano titanium dioxide; the composite adhesive layer is an adhesive coating including modified melanin powder and PVB adhesive.
[0035] The polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 1 part of modified sepiolite powder, 2 parts of SG-Al821, 1 part of ethylene-vinyl acetate copolymer, and 3 parts of stearic acid.
[0036] The modified sepiolite powder in the polyurethane layer is prepared by the following steps:
[0037] The sepiolite is calcined at 600°C for 1 hour, and after cooling, it is crushed in a ball mill and sieved to obtain nano-grade sepiolite powder; the sepiolite powder is added to a mixed solution of pentanediol and ethyl acetate with a mass concentration of 15%, and the mass ratio of pentanediol to ethyl acetate in the mixed solution is 3:1; the mixture is stirred and dispersed evenly to obtain a dispersion; then hydrochloric acid accounting for 2% of the mass of the dispersion is added to the dispersion, ultrasonically treated for 10 minutes, filtered, washed with deionized water, and dried to obtain modified sepiolite powder.
[0038] The modified polyurethane acrylate layer comprises modified polyurethane acrylate containing modified nano zinc oxide and modified nano titanium dioxide. The preparation steps of the modified polyurethane acrylate are as follows:
[0039] Add 0.5 parts of nano zinc oxide with a size of 60-80 nm and 0.5 parts of nano titanium dioxide with a size of 60-80 nm by weight to 2 parts of methyl methacrylate, 2 parts of n-butyl acrylate and 0.2 parts of n-octadecyl acrylate, and stir for 3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide; heat the solution to 80°C, add 0.05 parts of potassium persulfate and 5 parts of polyurethane acrylate with a functionality of 6-9, and react for 5 hours; then heat the solution to 100°C and react for 2 hours to obtain modified polyurethane acrylate.
[0040] The composite adhesive layer includes the following raw materials in parts by weight:
[0041] 15 parts of PVB adhesive, 20 parts of ethyl acetate, 3 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid.
[0042] The modified melanin powder in the composite adhesive layer is prepared by the following steps:
[0043] (1) 8 parts of melanin powder are uniformly dispersed in 80 parts of dimethyl sulfoxide by weight, 3 parts of sodium citrate are added, and the mixture is stirred and reacted at 130° C. for 60 minutes; 40 parts of n-butanol and 2 parts of dodecyl bromide are added, and the mixture is stirred and reacted at 100° C. for 60 minutes; 20 parts of polydimethylsiloxane and 3 parts of disodium ethylenediaminetetraacetate are added, and the mixture is stirred and reacted at 120° C. for 60 minutes; after the reaction is completed, the mixture is filtered, washed, and dried to obtain a primary product;
[0044] (2) Add 3 parts of the initial product to 10 parts of dimethylformamide, then add 2 parts of maleic anhydride, 3 parts of fumaric acid and 0.3 parts of citric acid, and stir at 70°C for 30 minutes; after the reaction is completed, filter, wash and dry to obtain modified melanin powder.
[0045] Example 2
[0046] Compared with Example 1, the present embodiment is different in that “the polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 1 part of modified sepiolite powder, 2 parts of SG-Al821, 1 part of ethylene-vinyl acetate copolymer, and 3 parts of stearic acid” is changed to “the polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 2 parts of modified sepiolite powder, 2 parts of SG-Al821, 1 part of ethylene-vinyl acetate copolymer, and 3 parts of stearic acid”; the remaining raw materials and preparation process remain the same as those in Example 1.
[0047] Example 3
[0048] Compared with Example 1, the present embodiment is different in that “the polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 1 part of modified sepiolite powder, 2 parts of SG-Al821, 1 part of ethylene-vinyl acetate copolymer, and 3 parts of stearic acid” is changed to “the polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 3 parts of modified sepiolite powder, 2 parts of SG-Al821, 1 part of ethylene-vinyl acetate copolymer, and 3 parts of stearic acid”; the remaining raw materials and preparation process remain the same as those in Example 1.
[0049] Example 4
[0050] Compared with Example 3, the present embodiment is different in that “adding 0.5 parts of nano zinc oxide with a size of 60-80 nm and 0.5 parts of nano titanium dioxide with a size of 60-80 nm by weight to 2 parts of methyl methacrylate, 2 parts of n-butyl acrylate and 0.2 parts of n-octadecyl acrylate and stirring for 3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide” is changed to “adding 1 part of nano zinc oxide with a size of 60-80 nm and 1 part of nano titanium dioxide with a size of 60-80 nm by weight to 2 parts of methyl methacrylate, 2 parts of n-butyl acrylate and 0.2 parts of n-octadecyl acrylate and stirring for 3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide”; the remaining raw materials and preparation process remain the same as those in Example 3.
[0051] Example 5
[0052] Compared with Example 4, this embodiment is different from Example 4 in that "15 parts of PVB adhesive, 20 parts of ethyl acetate, 3 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid" is changed to "15 parts of PVB adhesive, 20 parts of ethyl acetate, 4 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid"; the remaining raw materials and preparation process remain the same as those in Example 4.
[0053] Example 6
[0054] Compared with Example 4, this embodiment is different from Example 4 in that "15 parts of PVB adhesive, 20 parts of ethyl acetate, 3 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid" is changed to "15 parts of PVB adhesive, 20 parts of ethyl acetate, 5 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid"; the remaining raw materials and preparation process remain the same as those in Example 4.
[0055] Comparative Example 1
[0056] Compared with Example 1, the difference between this comparative example and Example 1 is that the nano zinc oxide and nano titanium dioxide are not modified, and "0.5 parts of nano zinc oxide with a size of 60-80 nm and 0.5 parts of nano titanium dioxide with a size of 60-80 nm are added to 2 parts of methyl methacrylate, 2 parts of n-butyl acrylate and 0.2 parts of n-octadecyl acrylate by weight, and stirred for 3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide; the solution is heated to 80°C, 0.05 parts of potassium persulfate and 5 parts of functional number The invention further comprises the following steps: “adding 0.5 parts of nano zinc oxide with a size of 60-80 nm, 0.5 parts of nano titanium dioxide with a size of 60-80 nm, 0.05 parts of potassium persulfate and 5 parts of polyurethane acrylate with a functionality of 6-9 to 80° C. for reaction for 5 h; and then heating to 100° C. for reaction for 2 h to obtain modified polyurethane acrylate” is changed to “adding 0.5 parts of nano zinc oxide with a size of 60-80 nm, 0.5 parts of nano titanium dioxide with a size of 60-80 nm, 0.05 parts of potassium persulfate and 5 parts of polyurethane acrylate with a functionality of 6-9 to 80° C. for reaction for 5 h; and then heating to 100° C. for reaction for 2 h to obtain modified polyurethane acrylate”; the remaining raw materials and preparation process remain the same as those in Example 1.
[0057] Comparative Example 2
[0058] The difference between this comparative example and Example 1 is that no modified sepiolite powder is added to the polyurethane layer; the other raw materials and preparation process remain the same as those in Example 1.
[0059] Comparative Example 3
[0060] The difference between this comparative example and Example 1 is that the "modified melanin powder" is replaced by "melanin powder" in the composite adhesive layer; the other raw materials and preparation process remain the same as those in Example 1.
[0061] The protective films prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to UV and blue light tests by sunlight irradiation; the pencil hardness of the films was measured by scratching the coatings with a pencil; the results are shown in Table 1:
[0062] Table 1
[0063] project UV blocking rate (%) Blue light blocking rate (%) hardness Example 1 90.6 85.6 4H Example 2 91.5 86.7 5H Example 3 92.4 87.5 6H Example 4 99.2 88.4 6H Example 5 99.4 93.3 6H Example 6 99.6 98.5 6H Comparative Example 1 70.4 84.3 3H Comparative Example 2 90.3 84.1 2H Comparative Example 3 88.2 60.9 4H
[0064] It can be seen from Table 1 that the protective films prepared in Examples 1 to 6 and Comparative Examples 1 to 3 all have excellent UV protection and blue light protection properties, and also have relatively high hardness.
[0065] Compared with Example 1 to Example 3, increasing the amount of modified sepiolite powder in the polyurethane layer is beneficial to improving the hardness of the protective film; compared with Example 3 and Example 4, increasing the amount of modified nano zinc oxide and modified nano titanium dioxide in the polyurethane acrylate layer is beneficial to improving the UV protection performance of the protective film; compared with Example 4 to Example 6, increasing the amount of modified melanin powder in the composite adhesive layer is beneficial to improving the blue light protection performance of the protective film.
[0066] Compared with Example 1, Comparative Example 1 shows that the protective film obtained by adding unmodified nano zinc oxide and nano titanium dioxide to the polyurethane acrylate layer has poor UV protection performance and reduced hardness; Compared with Example 1, Comparative Example 2 shows that the hardness of the protective film obtained by not adding modified sepiolite powder to the polyurethane layer is lower; Compared with Example 1, Comparative Example 3 shows that the protective film obtained by adding unmodified melanin powder to the composite adhesive layer has poor blue light protection performance.
[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-ultraviolet display screen protective film, characterized in that: The display screen protective film is a composite film composed of a polyurethane layer and a modified polyurethane acrylate layer, wherein the polyurethane layer and the modified polyurethane acrylate layer are composited with a composite adhesive layer; the modified polyurethane acrylate layer comprises modified nano zinc oxide and modified nano titanium dioxide; and the composite adhesive layer is an adhesive coating comprising modified melanin powder and PVB adhesive.
2. The UV-proof display screen protective film according to claim 1, characterized in that: The polyurethane layer comprises the following raw materials in parts by weight: 70 parts of polyurethane, 1-3 parts of modified sepiolite powder, 2 parts of coupling agent, 1 part of dispersant and 3 parts of lubricant.
3. The UV-proof display screen protective film according to claim 2, characterized in that: The modified sepiolite powder is prepared by the following steps: The sepiolite is calcined at 500-600°C for 1 hour, and after cooling, it is crushed in a ball mill and sieved to obtain nano-grade sepiolite powder; the sepiolite powder is added to a mixed solution of pentanediol and ethyl acetate with a mass concentration of 15%, stirred and mixed to uniformly disperse to obtain a dispersion; then hydrochloric acid accounting for 1-2% of the mass of the dispersion is added to the dispersion, ultrasonically treated for 5-10 minutes, filtered, washed with deionized water, and dried to obtain modified sepiolite powder.
4. The anti-ultraviolet display screen protective film according to claim 3, characterized in that: The mass ratio of pentanediol to ethyl acetate in the mixed solution of pentanediol and ethyl acetate is 3:
1.
5. The anti-ultraviolet display screen protective film according to claim 2, characterized in that: The coupling agent is one of SG-Al821, DL-411 and DL-411AF; The dispersant is ethylene-vinyl acetate copolymer; The lubricant is stearic acid.
6. The anti-ultraviolet display screen protective film according to claim 1, characterized in that: The modified polyurethane acrylate layer comprises modified polyurethane acrylate containing modified nano zinc oxide and modified nano titanium dioxide. The preparation steps of the modified polyurethane acrylate are as follows: Add 0.5-1 parts of nano zinc oxide and 0.5-1 parts of nano titanium dioxide by weight to 1-2 parts of methyl methacrylate, 1-2 parts of n-butyl acrylate and 0.1-0.2 parts of n-octadecyl acrylate, and stir for 2-3 hours to obtain a solution containing modified nano zinc oxide and modified nano titanium dioxide; heat the solution to 70-80°C, add 0.05 parts of potassium persulfate and 5 parts of polyurethane acrylate, and react for 3-5 hours; then heat the solution to 90-100°C and react for 1-2 hours to obtain modified polyurethane acrylate.
7. The anti-ultraviolet display screen protective film according to claim 6, characterized in that: The size of the nano zinc oxide is 60-80nm, and the size of the nano titanium dioxide is 60-80nm.
8. The UV-proof display screen protective film according to claim 6, characterized in that: The polyurethane acrylate has a functionality of 6-9.
9. The anti-ultraviolet display screen protective film according to claim 1, characterized in that: The composite adhesive layer comprises the following raw materials in parts by weight: 15 parts of PVB adhesive, 20 parts of ethyl acetate, 3-5 parts of modified melanin powder, 8 parts of bisphenol F epoxy resin, 3 parts of styrene, 2 parts of dimethyl itaconate, 3 parts of polydimethylsiloxane, 6 parts of polyvinyl alcohol, 2 parts of polyvinyl pyrrolidone and 3 parts of acrylic acid.
10. The anti-ultraviolet display screen protective film according to claim 9, characterized in that: The modified melanin powder is prepared by the following steps: (1) 8-10 parts of melanin powder are uniformly dispersed in 80 parts of dimethyl sulfoxide by weight, 1-3 parts of sodium citrate are added, and the mixture is stirred and reacted at 120-130° C. for 30-60 minutes; 30-40 parts of n-butanol and 1-2 parts of dodecyl bromide are added, and the mixture is stirred and reacted at 100° C. for 30-60 minutes; 10-20 parts of polydimethylsiloxane and 1-3 parts of disodium ethylenediaminetetraacetate are added, and the mixture is stirred and reacted at 120° C. for 30-60 minutes; after the reaction is completed, the mixture is filtered, washed, and dried to obtain a primary product; (2) adding 1-3 parts of the initial product to 8-10 parts of dimethylformamide, and then adding 1-2 parts of maleic anhydride, 1-3 parts of fumaric acid and 0.3 parts of citric acid, stirring and reacting at 60-70° C. for 20-30 minutes; after the reaction is completed, filtering, washing and drying to obtain modified melanin powder.
Citation Information
Patent Citations
Anti-ultraviolet blue light protection film
CN106863968A
Hydrophobic and light-resistant UV-LED curing oil polish for paper packaging printed matters
CN108373787A
Yellowing-resistant flame-retardant water-based UV woodware coating and preparation method thereof
CN109337533A
Anti-ultraviolet hardened film
CN114213961A
Sun-proof discoloration-resistant composite wood floor
CN115873497A